Predictors of new-onset distal neuropathic pain in HIV-infected individuals in the era of combination antiretroviral therapy. Issue 4 (April 2015) - Malvar, Jemily; Vaida, Florin; Sanders, Chelsea Fitzsimons; Atkinson, J. Hampton; Bohannon, William; Keltner, John; Robinson-Papp, Jessica; Simpson, David M.; Marra, Christina M.; Clifford, David B.; Gelman, Benjamin; Fan, Juanjuan; et al.
Abstract : Abstract: Despite modern combination antiretroviral therapy, distal neuropathic pain (DNP) continues to affect many individuals with HIV infection. We evaluated risk factors for new-onset DNP in the CNS Antiretroviral Therapy Effects Research (CHARTER) study, an observational cohort. Standardized, semiannual clinical evaluations were administered at 6 US sites. Distal neuropathic pain was defined by using a clinician-administered instrument standardized across sites. All participants analyzed were free of DNP at study entry. New-onset DNP was recorded at the first follow-up visit at which it was reported. Mixed-effects logistic regression was used to evaluate potential predictors including HIV disease and treatment factors, demographics, medical comorbidities, and neuropsychiatric factors. Among 493 participants, 131 (27%) reported new DNP over 2306 visits during a median follow-up of 24 months (interquartile range 12-42). In multivariable regression, after adjusting for other covariates, significant entry predictors of new DNP were older age, female sex, current and past antiretroviral treatment, lack of virologic suppression, and lifetime history of opioid use disorder. During follow-up, more severe depression symptoms conferred a significantly elevated risk. The associations with opioid use disorders and depression reinforce the view that the clinical expression of neuropathic pain with peripheral nerve disease is strongly influenced by neuropsychiatric factors. Delineating such risk factors might help target emerging preventive strategies, for example, to individuals with a history of opioid use disorder, or might lead to new treatment approaches such as the use of tools to ameliorate depressed mood. Abstract : Supplemental Digital Content is Available in the Text.Key predictors of new-onset distal neuropathic pain in HIV+ individuals during follow-up were past opioid use disorders and worsening depression symptoms.